Territorial rescaling and polycentric governance in Albania - Shutina, Dritan; Toto, Rudina (European Spatial Research and Policy, 2021)
Territories as relational geographical constructs are in constant formation and reformation, or rescaling, which results in spatial typologies of complex governance. The voting containers of a territory are merely one typology, often not matching the numerous functions within the other typologies. Under the assumption that voting containers are politically fixed, governance that adapts to the dynamics of territorial rescaling is required. This paper explores the relationship between territorial rescaling and polycentric governance in Albania. It concludes that polycentric governance can enable cooperation and efficiency throughout rescaling, assuming some conditions are in place for addressing the polycentricity gap.